Multimethod study of the degree of humification of humic substances extracted from different tropical soil profiles in Brazil's Amazonian region - Rosa, A. H.; Simoes, M. L.; de Oliveira, L. C.; Rocha, J. C.; Neto, L. M.; Milori, DMBP (Elsevier B.V., 2005)
This work consisted of determining the degree of humification of humic substances (HS) extracted from six different Amazonian soils collected from flooded and unflooded regions at different depths (0-10, 10-20, 20-40, and 60 cm). The humic substances were extracted according to procedures recommended by the International Humic Substances Society and characterized using elemental analysis, electron paramagnetic resonance (EPR), and fluorescence spectroscopy. The findings on semiquinone-type free radical concentrations in HS showed variations of 0.10-7.55x10(18) spins g(-1) of carbon (g C)(-1), indicating considerable differences between the humification levels of HS extracted from Amazonian soils. The results showed an average of 1.71 +/- 0.04 x 10(18) spins (g C)(-1), which is congruent with other data reported in the literature on Tropical soils. It was found that, on average, HS extracted from flooded soil contained higher semiquinone-type free radical concentrations than HS extracted from unflooded soils, indicating the influence of humidity in the humification process of organic matter. The humification process varies according to the profile, and the 10-20- and 0-10-cm profiles generally showed more humified HS. The degree of humification of the HS studied here displayed a similar behavior when exposed to fluorescence (excitation at 465 nm) and EPR (R=0.85). However, the low correlation between the C/H, C/O, and C/N atomic ratios and the semiquinone-type free radical concentration/fluorescence intensities indicated that data obtained by these techniques with regard to the degree of humification of HS may lead to different conclusions. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: soils; humic substances; elemental analysis; semiquinone-type free radicals; fluorescence spectroscopy; Amazonian region